Analisis Kesiapan Modernisasi Irigasi pada Daerah Irigasi Kewenangan Pemerintah Provinsi di Kabupaten Mojokerto - Sari, Dian Puspita; Anwar, Nadjadji; Sidharti, Theresia Sri (Balai Teknik Irigasi, 2019)
In carrying out irrigation system management in the irrigation area managed by the East Java Province in Mojokerto, PU Department of Water Resources of East Java experienced some constraint, namely irrigation infrastructure had expired, less of irrigation services and there was a decrease in storage capasity. Another constraint is population growth which has led to an increase in water use needs, food needs, conversion from agricultural land to settlements and industries and critical watersheds. In an effort to overcome these constraint, in addition to the operation, maintenance and rehabilitation, a comprehensive reform is needed, both institutional, technical, managerial, and human resources, known as irrigation modernization. Before carrying out irrigation modernization activities, it is necessary to have an assessment to measure the readiness levels of an irrigation area in carrying out modernization activities. First, determine the criteria that affect the modernization of irrigation, in this case there are 5 criteria and 34 sub criteria. Criteria weights were calculated using Fuzzy Analytical Hierarchy Process method. Then, priority scale of readiness irrigation area in carrying out irrigation modernization activities was determined using Simple Additive Weighting method. From 7 irrigation area managed by the East Java Province in Mojokerto, the resulting priority scale showed that modernization of irrigation can be applied to Kromong Irrigation Area. Modernization of irrigation should be postponed and carried out after revitalization on the Irrigation Area of Mernung, Sinoman, Penewon, Candi Limo, Jatikulon and Subontoro.